Ti‐Catalyzed Hydroamination for the Synthesis of Amine‐Containing π‐Conjugated Materials. Issue 21 (15th March 2018) - Hao, Han; Thompson, Kyle A.; Hudson, Zachary M.; Schafer, Laurel L.
Abstract: A series of conjugated enamines were prepared by Ti catalyzed anti‐Markovnikov hydroamination. The synthetic route is efficient with yields of up to 94 % and the 100 % atom efficiency of the reaction means that these products are easily isolated and purified. Due to the extended conjugated system, the enamine tautomers were observed exclusively in both solid and solution phases, as determined by X‐ray crystallography and NMR spectroscopy. These new conjugated molecules, with N incorporated into the backbone, show interesting photophysical properties including photo‐luminescent quantum yields of up to 0.26. Notably, through the incorporation of B to give a donor–acceptor π‐conjugated system, a redshift of approximately 100 nm is observed for the emission maximum along with the anticipated solvatochromic shifts. Abstract : Conjugated enamines were prepared through Ti catalyzed hydroamination with high isolated yields and purity. The structure was confirmed by NMR spectroscopy and X‐Ray crystallography. The photophysical properties were characterized and these molecules were found to bear high quantum yields and large solvatochromic shifts.